Foetal privacy. - Bellieni, Carlo V. (Medicina e Morale, 2004)
New clinical scenarios are appearing in prenatal medicine. In some cases their consequences are ominous for the offspring. Here we examine some effects of three sets: abuse of prenatal diagnosis with the aim of selecting possibly anomalous embryos, amniocentesis and in vitro fertilization. We discuss their drawbacks, the way they are performed, and the need of protecting the foetus who will bear the possible, though rare, drawbacks. In fact, though choise possibilities for parents are increasing, the guarantees of offspring are decreasing. The consequences of this "prenatal consumerism" are not only the suppression of the foetus, but the risk of disability for offspring. Then we deal with the problem of the intrusion in the privacy sphere of the foetus in the sphere of its genome and of its risk of having any illness in the course of his/her life. This information are rarely used to cure, often they are used to prevent the birth of a foetus with characteristics unwanted by parents. Are we facing a medical duty in the patients' interest or this is an abuse impossible to be performed unto an already born person? Once born, this information on his/her health will be no more a property only of the patient, but will be known by his/her parents and possibly by himself without his/her request. This information may be a risk for him/her from both the point of view of his/her possible prenatal suppression, and that of his/her self-awareness as he/she may know him/herself doomed to future tendencies or pathologies.